2020
DOI: 10.1002/nur.22060
|View full text |Cite
|
Sign up to set email alerts
|

Functional health literacy and caregiving burden among family caregivers of patients with end‐stage renal disease

Abstract: Family caregivers of patients with end‐stage renal disease (ESRD) experience significant caregiver‐related burden, yet the contribution of their functional health literacy (FHL) to caregiving burden has not been elucidated. We investigated the magnitude of FHL and caregiving burden and their association in a descriptive, correlational cross‐sectional study of family caregivers of Jordanian patients with ESRD (N = 88). The short versions of the FHL for Adults and the Zarit Burden Interview were used for assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 38 publications
1
29
1
1
Order By: Relevance
“…Four studies highlighted a negative correlation between CB and caregiver age [9,21,25,46]. In contrast, four studies reported that older caregivers have greater difficulty coping and experience higher levels of burden than younger caregivers [5,10,12,16,28,30,31,37,39]. Rodrigue et al [5] reported higher CB with increased caregiver age, although this study did not find a statistically significant correlation and suggested that further research is required, using a larger sample population to determine if a relationship exists.…”
Section: Caregiver and Patient Socio-demographical Factors Age Of Caregivers And Patients And Perceived Cbmentioning
confidence: 66%
See 4 more Smart Citations
“…Four studies highlighted a negative correlation between CB and caregiver age [9,21,25,46]. In contrast, four studies reported that older caregivers have greater difficulty coping and experience higher levels of burden than younger caregivers [5,10,12,16,28,30,31,37,39]. Rodrigue et al [5] reported higher CB with increased caregiver age, although this study did not find a statistically significant correlation and suggested that further research is required, using a larger sample population to determine if a relationship exists.…”
Section: Caregiver and Patient Socio-demographical Factors Age Of Caregivers And Patients And Perceived Cbmentioning
confidence: 66%
“…In this review, 38 studies investigated the level of CB in advanced stages of CKD patients and reported contrasting findings. Three studies reported high levels of burden [5,6,16]. The majority of the included studies reported moderate to severe levels of burden in caregivers of patients undergoing HD [9,10,18,20,21,27,30,32,34,37,39,46].…”
Section: Level Of Cbmentioning
confidence: 97%
See 3 more Smart Citations